Gender Mainstreaming in Budget Formulation in Bulukumba District in 2022 - Widya Astuti; Andi Yakub; Ariana Yunus (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Gender mainstreaming in the formulation of regional revenue and expenditure budgets in Bulukumba Regency has dynamics in its preparation. This research aims to analyze the policymakers' understanding of gender mainstreaming and the process of pulling interests in formulating the regional revenue and expenditure budget in Bulukumba Regency. The author conducted a case study research with a qualitative research base. Data was collected by interviewing key informants who could explain the process of formulating the regional revenue and expenditure budget regarding gender mainstreaming in Bulukumba Regency. The results of this study explain that there is a lack of institutional strengthening, especially in understanding gender mainstreaming. The budget is minimal and has not been able to cover all gender mainstreaming issues. Gender mainstreaming has not been a priority scale in government. The executive has been unable to reduce the budget for other programs, so the budget cannot cover gender mainstreaming. The preparation of the regional revenue and expenditure budget in Bulukumba Regency is inseparable from the role of several elites. This elite involvement then gave rise to several dynamics in the process of formulating the regional revenue and expenditure budget.